Pemberdayaan Masyarakat Melalui Desa Wisata Berbasis Pertanian - Kastowo, Chryssantus; Drajad, Hinggil; Sianipar, Stefani; Tio, Anastasia; Santoso, Theodora Yonna Effia; Fathoni,, Ifal; Dewi B B W, Sherin Kartika; Ari Wisnu Wijaya, Dionysius; Pratama Ganis, Andhika; Istiawan, Donny (Jurnal Atma Inovasia, 2022)
Community Service Program (Kuliah Kerja Nyata) is a form of devotion, awareness, and responsibility to society. This program aims to contribute in implementations from Tri Dharma of University and  learning tools to increase the empathy and ability of the students to understand the reality and all the problems who grow and thrive in society. This report made by society 5.0 concept which uses modern technology such as internet, conference video, and any other mobile tools, for both in the implementation of the programs and the data collecting process. This report uses 2 types of data, those are primary data and secondary data. The result of this program are in form of 1 report, 2 e-books and 2 videos in regard to tourism potency and the cultivation of brown rice in Desa Balong. This program could be used for improving public’s knowledge especially for the citizen in Desa Balong in order to develop and utilize the potency and all the natural resources there refers to the scientific paper that generated by this program.